Copper‐Catalyzed Asymmetric Alkylation of β‐Keto Esters with Xanthydrols. Issue 14 (7th October 2013) - Trillo, Paz; Baeza, Alejandro; Nájera, Carmen
Abstract The copper(II) triflate‐tert‐butyl‐bisoxazoline [Cu(OTf)2‐t‐Bu‐BOX]‐catalyzed asymmetric alkylation of β‐keto esters using free benzylic alcohols such as xanthydrols, as alkylating agents, is herein described for the first time. This green protocol renders in general the corresponding products with good results in terms of both yields and enantioselectivities using different keto esters, even when quaternary stereocenters were created. The scope, limitations and mechanistic aspects of the process are also discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>